MO815BEYOND SURVIVAL: COMPARISON OF HEMODIALYSIS AND CONSERVATIVE MANAGEMENT IN ELDERLY AND FRAIL STAGE 5 CHRONIC KIDNEY DISEASE PATIENTS. (29th May 2021) - Sala, Inês; Oliveira, João; Freitas, Joana; Tavares, Joana; Santos Lascasas, Josefina; Campos, Andreia; Castro, Ana; Cabrita, António
Abstract: Background and Aims: With the geriatric population increasing, the patients reaching stage 5 chronic kidney disease (CKD) are older, frailer and have multiple comorbidities. Technological advances in renal replacement therapy (RRT) and easier access to dialysis resulted in an expansion on geriatric dialysis population. Conservative management (CM) is an option that should be considered in this population, where is crucial to balance the survival and quality of life. Beside mortality, with this study we aim to evaluated patient-outcomes (hospitalization, falls and functional capacity) in older and frailer stage 5 CKD patients receiving hemodialysis (HD) and in CM. Method: We conducted a single center retrospective study in older (≥ 75years), frailer (Clinical Frailty Scale – CFS ≥ 5) and with multiple comorbidities (modified Charlson comorbidity index – mCCI ≥ 5 and) stage 5 CKD patients, admitted in our Nephrology department between January 1, 2014 to December 31, 2020. The eGFR was calculated through Chronic Kidney Disease Epidemiology Collaboration formula (CKD-EPI) at the time of decision or at the time of starting HD. The comorbidities were stratified using the mCCI and frailty was assessed with CFS at the time of decision in CM group (CMG) and at the start of HD (HDG). We evaluated hospitalizations, falls, CFS one-year later and survival in each group. Survival analysis was performed using the Kaplan–Meier method and was calculated at the beginning of RRT or eGFR ≤ 15ml/min/1.73m2 in CMG. Differences between the two groups were tested with Mann-Whitney U method. Results: A total of 76 patients with indication to start RRT were included: 61.8% (n=47) initiated HD and 38.2% (n=29) were in CM. The reasons for CM decision were deterioration of clinical condition (n=11), expected survival less than 6 months (n=8), patient option (n=5) and cognitive impairment (n=5). Clinical characteristics are presented in Table 1 . The CMG was older [median, IQR: 88 (85.5-90.5) vs 80 (77.0 – 83.0), p < 0.001] and had a lower BMI [23.44 (21.08 - 25.08) vs 26.23 (23.26 – 29.20), p=0.006]. Both groups did not differ significantly in terms of sex, CKD etiology, comorbidity or frailty. A total of 66 patients died at the end of the study [CMG 100% (n= 29) vs 78.7% HDG (n=37)]. The overall survival has higher on the HDG compared to the CMG with a median survival rate of 503 days (Fig 1 ). One-year survival rate was 53.5% in HDG vs 24% CMG (p <0.001). The median (IQR) of number of hospitalizations per patient was greater in the HDG [4 (1.5-6.5) vs 3 (0.5-5.5) CMG]. In HDG 17% patients had at least one fall vs 3.4% in CMG. In both groups there was a general deterioration associated to a higher CFS at one-year follow up (p=0.003 HD group vs p=0.015 CMG). Conclusion: In our study, hemodialysis was associated to improved survival in older and frailer stage 5 CKD patients compared to CM. However, this group had more hospitalizations, falls and poor functional status. These outcomes have a crucial impact on quality of life in this population and should be consider at the time of treatment decision. One of the limitations of our study was small sample size in both groups. In the future, we consider that is important to perform multicenter studies focused on patients-outcomes. We also think that it's important to understand the patient and family perspective in terms of quality of life and symptom burden associated to each treatment option.